The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/cvi.00286-15
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Reduced Interleukin-10 Levels to the Pathogenesis of Osteomyelitis in Children with Sickle Cell Disease

Abstract: Osteomyelitis is a significant complication of sickle cell disease (SCD), and several factors contribute to its pathogenesis, including altered expression of proinflammatory and anti-inflammatory cytokines. In view of the role of interleukin-10 (IL-10) as an anti-inflammatory cytokine, we tested the notion that SCD osteomyelitis is associated with a reduction in IL-10 secretion and, hence, precipitation of a proinflammatory state. Study subjects comprised 52 SCD patients with confirmed diagnosis of osteomyelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
3
2
Order By: Relevance
“…However, this finding differs from previous published studies, associating low IL-10 levels with vaso-occlusive crises, 16 osteomyelitis, 31 and acute chest syndrome 29 in patients with SCA. Furthermore, this contradicts a previous study showing that a lower serum IL-10 level is associated with ischemic stroke in the general population 32 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this finding differs from previous published studies, associating low IL-10 levels with vaso-occlusive crises, 16 osteomyelitis, 31 and acute chest syndrome 29 in patients with SCA. Furthermore, this contradicts a previous study showing that a lower serum IL-10 level is associated with ischemic stroke in the general population 32 …”
Section: Discussioncontrasting
confidence: 99%
“…Although not statistically significant, survival analysis ( Figure 2 ) suggested a trend toward acute cerebral ischemia protection in children carrying the haplotypes linked with low IL10 expression. However, this finding differs from previous published studies, associating low IL-10 levels with vaso-occlusive crises, 16 osteomyelitis, 31 and acute chest syndrome 29 in patients with SCA. Furthermore, this contradicts a previous study showing that a lower serum IL-10 level is associated with ischemic stroke in the general population.…”
Section: Discussioncontrasting
confidence: 99%
“…Conflicting reports are reported on the role of IL-10 in SCD patients. Sarray [21] demonstrated that changes in IL-10 serum levels is predicting VOC in SCD patients and his results clearly demonstrated a significant association between reduced IL-10 levels and the development of VOC and its severity. Patients undergoing Hydroxyurea therapy had high levels of IL-10 [10].…”
Section: Discussionmentioning
confidence: 95%
“…Decreased IL-10 values have been associated with an increased risk of OM since lower levels of the anti-inflammatory cytokine were reportedly noted in affected patients. 37 Future prospective studies could elaborate further on the link between IL-10 and OM in SCD and explore its role in OM diagnosis and follow-up.…”
Section: Discussionmentioning
confidence: 99%